Passages, the Marus manuscripts. Volume 1 - McCusker, Paul, 1958- (Carol Stream, Ill. : Tyndale House, 2012)
"What if a passage to a mysterious world opened up and beckoned you to play an important part in it's unfolding adventures? That's what happens to four kids from our world who find themselves caught up in the history changing events of another time and place. Yet there is something familiar about the people they encounter and their faith in the remarkable Unseen one"-- P. [4] of cover.
Darien's rise -- Arin's judgment -- Annison's risk.
Keywords: Brothers and sisters -- Juvenile fiction; Space and time -- Juvenile fiction; Christian life -- Juvenile fiction